Assessment of macrozoobenthic community dynamics in the Ijuk River: Implications for freshwater ecosystem health and conservation management - Jihanlillah, Adhestiasih Pangestu (Journal of Character and Environment, 2024)
Background: Nestled within the Isau-Isau Wildlife Reserve, the Ijuk River stretches approximately three kilometers, serving as a vital conservation area. Its upstream region plays multiple ecological roles, including watershed management, hydrological regulation, microclimate control, soil fertility maintenance, microbial habitat provision, air quality regulation, and carbon sequestration. However, escalating human activities, particularly changes in land use, pose significant threats to its ecological balance. The particular concern is the conversion of forested areas into agricultural lands, primarily for coffee cultivation and mixed gardens, encroaching dangerously close to the riverbanks. This encroachment necessitates a critical reevaluation of the river's water quality, given its crucial role in supporting biodiversity and ecological equilibrium. Benthic insects dwelling in the riverbed serve as invaluable bioindicators, offering insights into the overall health of aquatic ecosystems. Methods: Conducted between January and July 2022 in the Isau-Isau Wildlife Refuge, Lawang Agung Village, Mulak Ulu District, Lahat Regency, the study aimed to assess the macrozoobenthic community structure across three river segments: upstream, midstream, and downstream. Employing field sampling, observational surveys, taxonomic identification, and data analysis, the research aimed to unravel the river's ecological dynamics. Findings: Through meticulous examination of benthic insect communities, the study revealed relatively favorable water quality in the Ijuk River. However, discernible declines in various ecological parameters, as evidenced by evaluation results, highlight the urgency of conservation efforts and proactive management strategies to mitigate further degradation and preserve the river's ecological integrity. Conclusion: Such endeavors are crucial for safeguarding the biodiversity and sustainability of this vital freshwater ecosystem. Novelty/Originality of this Study: The study uniquely assesses the macrozoobenthic community dynamics in the Ijuk River, revealing significant changes over two decades that highlight the river's ecological health and underscore the urgent need for conservation efforts. It offers a comprehensive, updated evaluation of the macrozoobenthic community structure, providing critical insights into the impacts of land use changes and human activities on freshwater ecosystems.